2016
DOI: 10.1021/jacs.6b09349
|View full text |Cite
|
Sign up to set email alerts
|

Enabling Förster Resonance Energy Transfer from Large Nanocrystals through Energy Migration

Abstract: The stringent distance dependence of Förster resonance energy transfer (FRET) has limited the ability of an energy donor to donate excitation energy to an acceptor over a Förster critical distance (R) of 2-6 nm. This poses a fundamental size constraint (<8 nm or ∼4R) for experimentation requiring particle-based energy donors. Here, we describe a spatial distribution function model and theoretically validate that the particle size constraint can be mitigated through coupling FRET with a resonant energy migratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
94
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 111 publications
(95 citation statements)
references
References 58 publications
1
94
0
Order By: Relevance
“…revealed that, in homogenously doped LnNPs, only the near‐surface emitters contributed to FRET, whereas a major part of the near‐center lanthanide ions only transferred energy to acceptors through reabsorption processes . Consequently, this effect imposes a size constraint for the LnNPs because larger NPs increase the number of near‐center lanthanides beyond R 0 required for efficient nonradiative energy transfer (Figure b) . Additionally, energy transfer has to compete with other deactivation pathways, including radiative decay from the emission of the emitter and nonradiative deactivation through vibrational excitation of the host crystal lattice or surface defects/quenching sites.…”
Section: Energy‐transfer Mechanismsmentioning
confidence: 99%
See 3 more Smart Citations
“…revealed that, in homogenously doped LnNPs, only the near‐surface emitters contributed to FRET, whereas a major part of the near‐center lanthanide ions only transferred energy to acceptors through reabsorption processes . Consequently, this effect imposes a size constraint for the LnNPs because larger NPs increase the number of near‐center lanthanides beyond R 0 required for efficient nonradiative energy transfer (Figure b) . Additionally, energy transfer has to compete with other deactivation pathways, including radiative decay from the emission of the emitter and nonradiative deactivation through vibrational excitation of the host crystal lattice or surface defects/quenching sites.…”
Section: Energy‐transfer Mechanismsmentioning
confidence: 99%
“…We demonstrated that the gadolinium sublattice could assist an energy‐migration process to bridge energy transfer through the central particle–surface interface. This design allows us to realize more efficient FRET from a larger (≈30 nm) core–shell upconversion NP to FITC and many other dye molecules …”
Section: Energy Transfer From Lnnps To Dyesmentioning
confidence: 99%
See 2 more Smart Citations
“…The case of high sensitizer concentration, when the migration rate is faster than the spontaneous sensitizer decay or the sensitizer‐activator energy transfer, is called the fast migration case. Excitation energy could migrate over a relatively long range, covering the nanoparticle as a whole. As energy migration plays a very important role in upconversion luminescence, there have been many attempts to manipulate it in order to control the upconversion luminescence .…”
Section: Physical Formation Underlying Photophysics and Macroscopic mentioning
confidence: 99%